Decomposition rate of leaf litter between the protected and unprotected mangrove areas / Muhammad Fareed Zafri Mohd Salehin - Mohd Salehin, Muhammad Fareed Zafri (2019)
The decomposition rate of leaf litter between the protected (KKWRS) and unprotected (UiTM Sabah) mangrove areas were investigated during this study by using litter bags, where visibly both areas had different level of solid waste pollution where the unprotected area (UiTM Sabah) had high level of solid waste pollution. This study was conducted from March 2019 until July 2019. The mangroves species that was used in this study is Rhizophora mucronata, where the species is the dominant species in both mangrove areas. This study also focused on the factors that affect the decomposition rate of leaf litters, which are the soil organic matter and soil pH. Line transect and quadrat sampling was used to collect the soil samples and checked the soil pH. The leaf litter decomposition rate showed that the protected area (KKWRS) had faster decomposition rate compared to the unprotected area (UiTM Sabah). Soil organic matter and soil pH were higher at the unprotected area (UiTM Sabah) compared to the protected area (KKWRS). There is no correlation between both the soil organic matter (SOM) and soil pH to the leaf litter decomposition rate within the protected (KKWRS) and unprotected (UiTM Sabah) mangrove areas. In conclusion, both SOM and soil pH have no effect on the leaf decomposition rate within the protected (KKWRS) and unprotected (UiTM Sabah) mangrove areas.